(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In this present study, the hydrogeological (conditions) analysis of lithographic units of Northern Katsina State, Nigeria which comprises the thirteen (13) Local Government Areas was carried out. The research excludes sampling and laboratory experiment of water samples within the study areas, but a regional survey of water-bearing mediums and their physical characters. It therefore thought to review the previous drilling survey carried out by NGO’s in the past periods. The methodology adopted for the study was mainly secondary data. In the major findings in the areas, almost 85% of the total areas covered are underlain by rocks of the Basement Complex (BC) which have lesser yield, the remaining 15% are covered by Illo-Gundumi formation (Cretaceous) which is expected to have high yield and the Chad Basin formation with a very potential yield and which is also the youngest formation (Tertiary-Quaternary) It is recommended that hydrogeological investigations be done regularly to get up-to-date data for human and ecosystem development.